Caveolin-1 Scaffolding Domain Peptide Regulates Colon Endothelial Cell Survival through JNK Pathway - Kai Fang; Christopher G. Kevil (International Journal of Inflammation)
It has been reported that pathological angiogenesis contributes to both experimental colitis and inflammatory bowel disease. Recently, we demonstrated that endothelial caveolin-1 plays a key role in the pathological angiogenesis of dextran sodium sulfate (DSS) colitis. However, the molecular mechanism of caveolin-1 regulation of endothelial function is unknown. In this study, we examined how the antennapedia- (AP-) conjugated caveolin-1 scaffolding domain (AP-Cav) modulates vascular endothelial growth factor- (VEGF-) dependent colon endothelial cell angiogenic responses, as seen during colitis. We used mouse colon endothelial cells and found that AP-Cav significantly inhibited VEGF-mediated bromodeoxyuridine (BrdU) incorporation into colon microvascular endothelial cells. AP-Cav significantly blunted VEGF-dependent extracellular signal-regulated kinase 1/2 (ERK 1/2) phosphorylation at 10 minutes and 2 hours after stimulation, compared with the AP control peptide. AP-Cav + VEGF-A treatment also significantly increased c-Jun N-terminal kinase (JNK) phosphorylation at 2 hours. AP-Cav + VEGF-A treatment significantly downregulated retinoblastoma (Rb) protein levels, upregulated cleaved caspase-3 protein levels at 4 hours, and induced apoptosis. Thus, our study suggests that disruption of endothelial caveolin-1 function via the AP-Cav diverts VEGF signaling responses away from endothelial cell proliferation and toward apoptosis through the inhibition of mitogen-activated protein (MAP) kinase signaling and the induction of JNK-associated apoptosis.